Emotional Nuance: Examining Positive Emotional Granularity and Well-Being - Tan, Tse Yen; Wachsmuth, Louise; Tugade, Michele M. (Frontiers in Psychology, 2022)
The focus of this review is on positive emotional granularity. Emotional granularity is the level of specificity that characterizes verbal representations of an affective experience (Barrett, 2004). Although there has been research on negative emotional granularity (Kashdan et al., 2015), relatively less attention has been given to the study of positive emotional granularity. Positive emotions are theorized to motivate an individual to "broaden and build" one's scope of cognition, attention, and behavior (Fredrickson, 2001; Tugade et al., 2004). Distinct positive emotion concepts may provide individuals with more informational value than that provided by global mood. Indeed, individuals who are higher in positive emotional granularity report being better at coping with stressful experiences (Tugade et al., 2004). In this review, we discuss growing research on positive emotional granularity and well-being. Issues of measurement, interventions, and considerations for future lines of research are discussed.